KEBIJAKAN PENGELOLAAN RUANG TERBUKA HIJAU (RTH) TAMAN FLORA SURABAYA - Nila Rosawatiningsih (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The high interest of the community specifically for tourism activities makes the city government must innovate by developing Green Open Space (RTH) as a place that has complex facilities. The Green Open Space (RTH) provided by the city of Surabaya is the Flora Park which is also a big city park with complete supporting facilities. This review also describes what activities people do when visiting the Flora Park so as to produce social structures that are interrelated and cannot be completed. The method used in this study is qualitative and descriptive analysis. Research results on the functions of Flora Park are very complex discussing the functions of education, health functions, financial functions and interaction functions. All these functions can work because visitors, the government, the private sector, managers, traders and the community carry out their roles according to them status. The role that each structure carries out has a huge influence on the existence and development of Taman Flora Surabaya.